From tool-making to tool-using – and back: rationales for adoption and use of LCC - Gluch, Pernilla; Gustafsson, Mathias; Baumann, Henrikke; Lindahl, Göran (International Journal of Strategic Property Management, 2018)
Real estate- and property owners’ rationales behind the adoption of Life Cycle Costing (LCC) respectively how LCC is actually used in renovation projects, is investigated through empirical data from a questionnaire survey sent to managers in Swedish real estate organisations. The study shows a positive attitude towards LCC. It is perceived to as a flexible and multi-functional tool with a familiar monetary format. Nevertheless, the study also reveals simplistic and undevel-oped views of how to use LCC. While much research has focused on developing sophisticated LCC tools, the findings indicate that practitioners’ interest in these refinements seems limited. The importance of understanding that LCC is used in a context of multiple and partly competing institutional logics of renovation is emphasised. The paper contributes to a more informed research in development of LCC tools as well as better informed LCC use among real estate and property owners.